Exclusive intraoperative radiotherapy for invasive breast cancer in elderly patients (>70 years): proportion of eligible patients and local recurrence-free survival. Issue 1 (December 2016) - Lambaudie, Eric; Houvenaeghel, Gilles; Ziouèche, Amira; Knight, Sophie; Dravet, François; Garbay, Jean; Giard, Sylvie; Charitansky, Hélène; Cohen, Monique; Faure, Christelle; Hudry, Delphine; Azuar, Paul; et al.
Abstract Background To estimate the proportion of elderly patients (>70 years) with breast cancer eligible for an Exclusive IntraOperative RadioTherapy (E-IORT) and to evaluate their local recurrence-free survival rate. Methods This retrospective study examining two cohorts focuses on patients over 70 years old: a multi-centric cohort of 1411 elderly patients and a mono-centric cohort of 592 elderly patients. All patients underwent conservative surgery followed by external radiotherapy for T0-T3 N0-N1 invasive breast cancer, between 1980 and 2008. Results Within each cohort two groups were identified according to the inclusion criteria of the RIOP trial (R group) and TARGIT E study (T group). Each group was divided into two sub-groups, patients eligible (E) or non-eligible (nE) for IORT. The population of patients that were eligible in the TARGIT E study but not in the RIOP trial were also studied in both cohorts. The proportion of patients eligible for IORT was calculated, according to the eligibility criteria of each study. A comparison of the 5-year local or locoregional recurrence-free survival rate between eligible vs non-eligible patients was made. In both cohorts, the proportion of patients eligible according to the RIOP trial's eligibility criteria was 35.4 and 19.3%, and according to the TARGIT E study criteria was 60.9 and 45.3%. The 5-year locoregional recurrence-free survival rate was not significantly different between RE and RnE groups, TE and TnE groups. In both cohorts RE and (TE-RE) groups were not significantly different. Conclusions Our results encourage further necessary studies to define and to extend the eligibility criteria for per operative exclusive radiotherapy.